Effects of additional vitamin E and selenium supply on antioxidative defence mechanisms in the kidney of rats treated with high doses of glucocorticoid - Beytut, E; Erisir, M; Aksakal, M (Wiley, 2004)
The aim of this work was to determine the effects of dietary vitamin E and selenium (Se) on lipid peroxidation as thiobarbituric acid reactive substances (TBARS) and on the antioxidative defence mechanisms in the kidney of rats treated with high-doses of prednisolone. Two hundred and fifty adult male Wistar rats were randomly divided into five groups. The rats were fed a normal diet, but groups 3, 4, and 5 received a daily supplement in their drinking water of 20 mg vitamin E, 0.3 mg Se, and a combination of vitamin E and Se, respectively, for 30 days. For 3 days subsequently, the control group (group 1) was treated with a placebo, and the remaining four groups were injected intramuscularly with 100 mg kg(-1) body weight (bw) prednisolone. After the last administration of prednisolone, 10 rats from each group were killed at 4, 8, 12, 24, and 48 h and the activities of glutathione peroxidase (GSH-Px) and catalase (CAT) enzymes, and the levels of glutathione (GSH) and TBARS in their kidneys were measured. GSH-Px and CAT enzyme activities and GSH levels in the prednisolone treatment group (group 2) began to decrease gradually at 4h, falling respectively to 48 and 65% of the control levels by 24h, and recovering to the control levels at 48 h. In contrast, prednisolone administration caused an increase in TBARS in the kidneys, reaching up to twice the levels of the control group at 24 h. However, supplementation with vitamin E and Se had a preventive effect on the elevation of kidney TBARS and improved the diminished activities of the antioxidative enzymes and the levels of GSH. Therefore, the present study demonstrates the effectiveness of vitamin E and Se in reducing kidney damage in glucocorticoid-treated rats and suggests that reductions in increased TBARS due to prednisolone may be an important factor in the action of vitamin E and Se. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: toxic dose of glucocorticoid; kidney; lipid peroxidation; glutathione peroxidase; catalase; glutathione